AN ALTERNATIVE VIEW OF THE ISRAEL-PALESTINE DISPUTE: THE ESCHATOLOGICAL DIMENSION - Glen Segell (CMES (Center of Middle Eastern Studies), 2023)
This article examines the Israel-Palestine conflict through the lens of eschatology, a religious belief concerning end-of-age expectations, which often incites violent reactions. Despite extensive research on the Israel-Palestine conflict, there is a lack of comprehensive studies exploring the role of eschatology in this context. The Middle East, including Israel and Palestine, is a turbulent war zone with religion significantly fueling extreme hatred and violence. The focus is on the impact of religious traditions, particularly eschatology, which is prone to provoke violent reactions. The study analyzes this through five sections: eschatology prophecy, daily religion, Jerusalem’s role, expansion beyond Jerusalem, and the conveyed message. The article concludes that eschatology significantly influences this conflict, with violent apocalyptic prophecies exacerbating the situation. Resolving this conflict necessitates diverse interpretations of eschatology and apocalyptic prophecies and understanding religion’s role in the conflict.